Partição de massa seca, produção e qualidade de morango em função do sistema de fertirrigação e da origem das mudas - Webler, Anderson Rafael (2019)
The success of strawberry cultivation depends on several factors, such as the quality of the seedlings and their adaptation to the growing site, as well as the management and fertigation system used. Thus, the objective was to study the influence of the fertigation system and the origin of the seedlings on the growth, production and strawberry quality of the Albion cultivar in two subsequent crops. To growth and dry mass study, two experiments were carried out in a randomized complete block design (RBD), in a 2x2x15 trifatorial scheme. The first two origins of the seedlings (national and imported), two fertirrigation systems (open and closed system) and 15 plant evaluations during the cultivation and in the second experiment, two fertigation systems, two cultivation periods and 15 evaluations. It was evaluated the dry mass accumulation of root, stem, leaves, senescent leaves, flowers, commercial fruits and non-commercial fruits, besides root volume, root length, number of leaves, number of flowers, number of fruits commercial and non-commercial. In the first experiment there was a significant difference for dry mass, root length and volume, as well as senescent leaves, with higher plant mean values from imported seedlings. Dry mass and number of commercial and non-commercial fruits were higher under national seedlings, while other factors were significant only among the evaluations. In the second experiment there was a difference between the years of cultivation, with the first one being the dry mass, root volume and length, leaf number, leaf area, dry mass and number of senescent leaves and flowers. In general, we observed a constant increase of the variables evaluated until the last evaluation, at 196 days after transplantation. For the production and quality analysis, two experiments were carried out in RBD in a 2x2 factorial scheme, the first one with two origins of the seedlings (national and imported), and two fertirrigation systems (open and closed) and the second comparing the two fertigation systems in two crops. The productive variables (yield, number of fruits per plant and average mass of fruits) and qualitative variables (total soluble solids (TSS), titratable acidity (TA), and TA/TSS ratio) were evaluated. In the first experiment, the national seedlings and the open fertirrigation system presented higher productivity and number of fruits per plant. In the second, the open fertirrigation system presented higher yield, without difference in the second crop for the number of fruits. From the qualitative variables, only TA presented a difference between the fertirrigation systems, with the highest average in the closed system, in the first experiment, while in the second there were differences between the cultivars for TA and TSS, with higher averages in the first one. Thus, it is recommended the cultivation of seedlings of national origin and further research on the viability of the closed fertigation system, since it presented a lower than open production result.